An application of the stress state decomposition technique (Ssdt) to cancer modelling - Di Rado, Héctor Ariel (2021)
Fil: Beneyto, Pablo Alejandro. Universidad Nacional del Nordeste. Facultad de Ingeniería; Argentina.